(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Functional Parts of Speech This article is introductory to functional parts of speech in the way that it describes how the various parts of speech perform different functions in sentence structure and meaning. The main categories observed in this text include nouns, verbs, adjectives, adverbs, pronouns, conjunctions, prepositions, and interjections. Each of these has a review in the sense of communication. Functional parts of speech are related to describing how words work together within sentences, putting emphasis on word relations and grammatical features. It also explores open versus closed word classes, considering that open word classes are those that grow with the development of languages, such as nouns and verbs, while the closed word classes are the words that remain relatively fixed, like prepositions and conjunctions. This gives basis for the way in which words interrelate in a sentence to provide both grammar and semantics.